Gambaran Resiliensi Narapidana di Lapas Perempuan Kelas IIB Padang - Donna Aryati; Devi Ruslin (CAUSALITA : Journal of Psychology, 2025)
A prisoner is defined as someone who has violated societal norms and received a legal decision resulting in the deprivation of their freedom, leading to the loss of personal independence. As a consequence, they serve their sentence in a correctional facility. Imprisonment can lead to various issues, such as inner conflict, irritability, anxiety, boredom due to routine activities in prison, longing for family, difficulty adapting, and unpreparedness in facing reality.Therefore, individuals in such conditions must develop resilience. Resilience refers to the ability to cope with and adapt to difficult situations or life challenges, including enduring pressure and overcoming suffering or trauma experienced throughout life.This study aims to explore resilience among inmates at Class IIB Padang Correctional Facility. The research employs a qualitative approach by distributing surveys using an open-ended questionnaire, divided into three stages: preparation, development, and implementation.The findings illustrate various factors contributing to resilience among inmates in the Class IIB Women's Correctional Facility in Padang. A total of 25 factors were identified, with the three most significant being family support, sentence duration, and acceptance (sincere acceptance of their situation). Additionally, the study highlights activities that help inmates maintain resilience, including sports, religious practices, and artistic activities.The study also indicates that demographic factors such as age, education level, length of sentence, and occupation influence inmates' resilience.